The impact of user fees on uptake of HIV services and adherence to HIV treatment: Findings from a large HIV program in Nigeria - Ahonkhai, Aima A.; Regan, Susan; Idigbe, Ifeoma; Adeniyi, Olayemi; Aliyu, Muktar H.; Okonkwo, Prosper; Adeola, Juliet; Losina, Elena; Musa, Zaidat; Ezechi, Oliver; Freedberg, Kenneth A. (PLOS ONE, 2020)
Background Global HIV funding cutbacks have been accompanied by the adoption of user fees to address funding gaps in treatment programs. Our objective was to assess the impact of user fees on HIV care utilization and medication adherence in Nigeria. Methods We conducted a retrospective analysis of patients enrolled in care before (October 2012-September 2013) and after (October 2014-September 2015) the introduction of user fees in a Nigerian clinic. We assessed pre- vs. post-user fee patient characteristics and enrollment trends, and determined risk of care interruption, loss to follow-up, and optimal medication adherence. Results After fees were instituted, there was a 66% decline in patient enrollment and 75% decline in number of ART doses dispensed. There was no difference in the proportion of female clients (64% vs 63%, p = 0.46), average age (36 vs. 37 years, p = 0.15), or median baseline CD4 (220/ul vs. 222/uL, p = 0.24) in pre- and post-fee cohorts. There was an increase in clients employed and/or had tertiary education (24% vs. 32%, p<0.001). Compared to pre-fee patients, the post-fee period had a 48% decreased risk of care interruption (aRR = 0.52, 95%CI:0.39–0.69), 22% decreased LTFU risk (aRR = 0.64, 95%CI:0.96), and 27% decreased odds of optimal medication adherence (aOR = 0.7, 3 95%CI 0.59–0.89). Conclusions Patients enrolled in care after introduction of user fees in Nigeria were more likely to be educated or employed, and effectively retained in care after starting ART. However, fees were accompanied by a drastic reduction in new patient enrollment, suggesting that many patients may have been marginalized from HIV care.